Excessive umbilical cord coiling confers risk of elevated nocturnal blood pressure and severe/early-onset preeclampsia. Issue 1 (January 2019) - Lv, Li-Juan; Wu, Lin-Lin; Wen, Ji-Ying; Lei, Qiong; Miao, Jun; Duan, Hong-Li; Ji, Wen-Jie; Duan, Dong-Mei; Luo, Yi-Fei; Xiao, Li; Li, Bin; Li, Yu-Ming; et al.
Abstract : Background: The associations between umbilical cord coiling, feto-placental vascular resistance and maternal blood pressure (BP) are not well understood. Method: We retrospectively analyzed 502 pregnant women suspected of hypertensive disorders in the third trimester from a hospital-based cohort, who underwent ambulatory BP monitoring and umbilical artery Doppler velocimetry examinations within 14 days before delivery. By applying quantile regression, a significant quantile-dependent positive association between umbilical cord coiling index and umbilical artery pulsatility index (UAPIMOM ; converted to multiples of median) was observed from above 0.75th quantiles for each parameter. Results: Using the cutoffs both at the 0.75th quantile to define high umbilical cord coiling (≥0.28 coils/cm) and high UAPIMOM (≥1.30), respectively, a graded increase in BP level was observed from patients with both low, either high and both high categories. Multivariate linear and quantile regression revealed that the high umbilical cord coiling/high UAPIMOM interaction was significantly correlated with night-time mean DBP level. Moreover, umbilical cord hypercoiling (≥0.3 coils/cm) was significantly correlated with night-time DBP with an average increase of ∼5 mmHg from the 0.05th to 0.70th quantiles and independently predicted the occurrence of severe (odds ratio 2.32, 95% confidence interval: 1.22–4.41) and early-onset (odds ratio 2.43, 95% confidence interval: 1.18–4.97) preeclampsia after adjusting for covariates. Further mediation analysis showed that elevated high UAPIMOM (≥1.30) could explain 11.4% of the umbilical cord hypercoiling → high night-time DBP association. Conclusion: Therefore, this retrospective study identifies excessive umbilical cord coiling, and its interaction with increased feto-placental vascular resistance, as novel risk factors for nocturnal BP elevation and preeclampsia. Abstract : Supplemental Digital Content is available in the text